(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article analyses how structure and topics presented in the online performance Tudo que coube numa VHS by Grupo Magiluth address the spectator regarding the psico-social context created by the Covid-19 pandemia. It asks how these formal and thematic traits relate to unstable social relations and excited subjectivities as elements through which the capitalist system nowadays sustains its functioning. Within this focus, the article analyses the tecnocomunal proposal that designs this online performance as an example of a production of events and pseudo-events, molded by the tension between escapist and transformative gestures.